2016
DOI: 10.1614/ws-d-16-00064.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed Community Dynamics and System Productivity in Alternative Irrigation Systems in California Rice

Abstract: Over the last 10 yr, California has experienced a series of ever-worsening droughts. Rice, traditionally a flooded crop, has come under increasing scrutiny with respect to its water use, leading to proposals to evaluate alternative irrigation systems. For growers, weed competition is one of the most limiting factors to maintaining high yields, so understanding the shifts among species in weed communities under the proposed alternative irrigation systems is vital. A field study was conducted from 2012 to 2014 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…When comparing the average of the two populations, there was variation between treatments, with significantly less emergence occurring in the continuously flooded treatment compared to the intermittent flush and daily flush treatments (Figure 3), although differences were not significant between populations. This is consistent with field data with watergrass species, where shifting irrigation to flooding can be used to suppress watergrass populations (Brim-DeForest et al 2017;Pittelkow et al 2012). It is also consistent with the emergence data reported by Boddy et al (2012a), where both flooding and intermittent irrigation reduced emergence of both HR and RD populations.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…When comparing the average of the two populations, there was variation between treatments, with significantly less emergence occurring in the continuously flooded treatment compared to the intermittent flush and daily flush treatments (Figure 3), although differences were not significant between populations. This is consistent with field data with watergrass species, where shifting irrigation to flooding can be used to suppress watergrass populations (Brim-DeForest et al 2017;Pittelkow et al 2012). It is also consistent with the emergence data reported by Boddy et al (2012a), where both flooding and intermittent irrigation reduced emergence of both HR and RD populations.…”
Section: Resultssupporting
confidence: 90%
“…Koss; synonym Echinochloa oryzicola Vasinger) is one of the most competitive weeds in the California rice agroecosystem, reducing yields up to 59% when uncontrolled (Gibson et al 2002). Recent data suggest that losses may be higher in dry-seeded systems (Brim-DeForest et al 2017). In California, late watergrass germinates and emerges under both aerobic and anaerobic conditions (Boddy et al 2012a;Linquist et al 2008;Pittelkow et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, AWD can increase weed density (Figure 4D) if farming practices are not coupled with appropriate weed management interventions (Brim-DeForest et al, 2017;Samoy-Pascual et al, 2020). Some studies done in Nepal reported that AWD restricts the proliferation of weeds due to its soil contraction effects (Howell et al, 2015).…”
Section: Trade-off and Cross-scale Issuesmentioning
confidence: 99%
“…Weed management practices impose selection pressures that drive shifts in weed communities. Documented cases of weed shifts due to changes in weed management have occurred as a result of tillage, irrigation systems, herbicide use, and crop rotation (Brim-DeForest et al 2017;Davis et al 2009;Johnson and Coble 1986;Johnson et al 2009;Menalled et al 2001;Tuesca et al 2001). Shifts in weed species have also been observed when comparing glyphosate-resistant cropping systems with conventional herbicide systems.…”
Section: Introductionmentioning
confidence: 99%